Alternatif Diversifikasi Pengolahan Jamur Tiram Putih (Pleurotus Ostreatus) menjadi Tepung Jamur - Retno Wulan Damayanti; Cucuk Nur Rosyidi; Ilham Priadythama; Azizah Aisyati (Industrial Engineering Study Program, Faculty of Engineering, Universitas Sebelas Maret, 2014)
Oyster mushroom is one of the most popular mushroom consumption cultivated in Indonesia. The cultivation process of oyster mushrooms is relatively easy , and also marketable because it has the nutrients and good nutrition. Oyster mushrooms is perishable foodstuffs. A few days after harvesting, oyster mushrooms will be amended, color changes to brown, becoming soft texture, and appeared unpleasant aroma. To overcome this, it is necessary to oyster mushroom processing innovation into alternative food products that have high sales value and longer shelf life. One alternative diversification of processed fresh oyster mushrooms is powdery mildew . To cultivate oyster mushrooms into powdery mildew, in this study focus to design a dryer oyster mushrooms with solar energy ( Solar dryer) and applying the grinder. Drier and grinder oyster mushrooms was tested in groups of oyster mushroom farmers in the Tambak village Boyolali . Solar drier, can drying fresh oyster mushrooms with a capacity of 10 kg within a period of 50-72 hours. Oyster mushrooms grinder can be used with a capacity of 120 grams with a flouring 180 seconds